Close your eyes and count to 10 [large type] - Unger, Lisa, 1970- (Thorndike Press large print dynamic drama., 2025)
"Extreme adventurer Maverick Dillan invites you to the ultimate game of hide-and-seek. But as the players gather on Falcão Island, the event quickly spirals into a chilling test of survival. A storm rages as a deadly threat stalks the contestants, turning the challenge into something far more sinister than the social media stunt it was intended to be. Enter Adele, a single mother with a fierce determination to protect her children at all costs. When she begins the game, she unwittingly enters a twisted web of deception and intrigue. Can she maneuver through the treacherous storm and the relentless competition and get home to her family?"--